Hegelian analytic philosophy: P. Redding’s reading of Hegel - Bavaresco, Agemir; Cooper, Andrew (ENDOXA, 2013)
The classic analytic tradition associated the philosophy of George Berkeley with idealism. Yet in terms of the German Idealismus, Berkeley was no idealist. Rather, he described himself as an “immaterialist”. In the classic analytic tradition we find a misunderstandingof the German Idealismus. This paper will suggest, through reference to the work of Paul Redding, that Hegel’s Phenomenology of Spirit presents Idealismus as that which reconciles objectivity and subjectivity in the experience of consciousness. Hegel’s Phenomenology develops this idea in the elaboration of a remarkably novel theory of consciousness. For Hegel, the conditions of the possibility of the objects of experience are a dialectical movement between consciousness and the object, or immediacy and mediacy. In the whole movement of consciousness we have the logic of contradiction working at the back of phenomenological experience that Hegel will make explicit in the Science of Logic, a logic that involves the thinker becoming consciously aware of their ownthought processes. Yet Hegel’s Logic is different from the common meaning of ‘logic’. His Logicis not a formal approach to valid inference but captures the method and the moments and movementof logic. For Hegel, the great problem of classical logic is the immobility of the categories. This paper proposes that Hegel’s ‘holism’ entails the description where in Logic, Nature, and Spirit are articulated as a whole in dialectical movement.